Brain volumes differ between diagnostic groups of violent criminal offenders - Bertsch, Katja; Grothe, Michel; Prehn, Kristin; Vohs, Knut; Berger, Christoph; Hauenstein, Karlheinz; Keiper, Peter; Domes, Gregor; Teipel, Stefan; Herpertz, Sabine (European archives of psychiatry and clinical neuroscience, 2013)
Studies on structural abnormalities in antisocial individuals have reported inconsistent results, possibly due to inhomogeneous samples, calling for an investigation of brain alterations in psychopathologically stratified subgroups. We explored structural differences between antisocial offenders with either borderline personality disorder (ASPD-BPD) or high psychopathic traits (ASPD-PP) and healthy controls (CON) using region-of-interest-based and voxel-based morphometry approaches. Besides common distinct clusters of reduced gray matter volumes within the frontal pole and occipital cortex, there was remarkably little overlap in the regional distribution of brain abnormalities in ASPD-BPD and ASPD-PP, when compared to CON. Specific alterations of ASPD-BPD were detected in orbitofrontal and ventromedial prefrontal cortex regions subserving emotion regulation and reactive aggression and the temporal pole, which is involved in the interpretation of other peoples’ motives. Volumetric reductions in ASPD-PP were most significant in midline cortical areas involved in the processing of self-referential information and self-reflection (i.e., dorsomedial prefrontal cortex, posterior cingulate/precuneus) and recognizing emotions of others (postcentral gyrus) and could reflect neural correlates of the psychopathic core features of callousness and poor moral judgment. The findings of this first exploratory study therefore may reflect correlates of prominent psychopathological differences between the two criminal offender groups, which have to be replicated in larger samples.
Gesehen am 24.11.2020